1931
DOI: 10.1001/archpedi.1931.01940140054004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteins and Edema

Abstract: In health, about four fifths of the solids of the plasma consist of plasma proteins. Their approximate percentages are as follows: total protein, from 7 to 8; albumin, from 4 to 5; globulin, from 1.5 to 3.5; fibrinogen, from 0.1 to 0.25; albumin-globulin ratio, 37.The colloidal osmotic pressure of the blood plasma is from 25 to 30 mm. of mercury and is maintained largely by the plasma proteins, as was first revealed by Starling.1 The colloidal osmotic pressure of the blood plasma (the totality of pressure with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1933
1933
1939
1939

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…and it has been suggested that it may be correlated with an effort of the organism to compensate for the decrease in osmotic pressure following the loss of serum protein (FISHBERG). This, however, has not been confirmed and CALVIN and GOLDBERG (24) who, in children presenting the nephrotic syndrome, found in general that as the oedema increased the cholesterol increased and the albumin decreased, are not prepared to subscribe to the idea that the increased blood cholesterol is a compensatory mechanism in view of the variations observed. There is thus no direct evidence that the lipaemia has any relation to oedema, and on the whole HILLER's suggestion seems the most probable.…”
Section: Schade Andmentioning
confidence: 91%
See 1 more Smart Citation
“…and it has been suggested that it may be correlated with an effort of the organism to compensate for the decrease in osmotic pressure following the loss of serum protein (FISHBERG). This, however, has not been confirmed and CALVIN and GOLDBERG (24) who, in children presenting the nephrotic syndrome, found in general that as the oedema increased the cholesterol increased and the albumin decreased, are not prepared to subscribe to the idea that the increased blood cholesterol is a compensatory mechanism in view of the variations observed. There is thus no direct evidence that the lipaemia has any relation to oedema, and on the whole HILLER's suggestion seems the most probable.…”
Section: Schade Andmentioning
confidence: 91%
“…One such theory is that advanced by CALVIN and GOLDBERG (24) who postulate some °trigger, mechanism of unknown origin,"…”
Section: Schade Andmentioning
confidence: 99%